PH deregulation as the eleventh hallmark of cancer. (2023) - Koltai, Tomas; Fliegel, Larry; Reshkin, Stephan J; Baltazar, Fátima; Cardone, Rosa Angela; Alfarouk, Khalid Omer; Afonso, Julieta
No abstract available